Nuclear Factor I‐C acts as a regulator of hepatocyte proliferation at the onset of liver regeneration. (25th October 2014) - Edelmann, Simone; Fahrner, René; Malinka, Thomas; Song, Bryan H.; Stroka, Deborah; Mermod, Nicolas
Abstract Background & Aims Knockout studies of the murine Nuclear Factor I‐C (NFI‐C) transcription factor revealed abnormal skin wound healing and growth of its appendages, suggesting a role in controlling cell proliferation in adult regenerative processes. Liver regeneration following partial hepatectomy (PH) is a well‐established regenerative model whereby changes elicited in hepatocytes lead to their rapid and phased proliferation. Although NFI‐C is highly expressed in the liver, no hepatic function was yet established for this transcription factor. This study aimed to determine whether NFI‐C may play a role in hepatocyte proliferation and liver regeneration. Methods Liver regeneration and cell proliferation pathways following two‐thirds PH were investigated in NFI‐C knockout (ko) and wild‐type (wt) mice. Results We show that the absence of NFI‐C impaired hepatocyte proliferation because of plasminogen activator I (PAI‐1) overexpression and the subsequent suppression of urokinase plasminogen activator (uPA) activity and hepatocyte growth factor (HGF) signalling, a potent hepatocyte mitogen. This indicated that NFI‐C first acts to promote hepatocyte proliferation at the onset of liver regeneration in wt mice. The subsequent transient down regulation of NFI‐C, as can be explained by a self‐regulatory feedback loop with transforming growth factor beta 1 (TGF‐ß1), may limit the number of hepatocytes entering the first wave of cell division and/or prevent late initiations of mitosis. Conclusion NFI‐C acts as a regulator of the phased hepatocyte proliferation during liver regeneration.